Rangkap Jabatan Anggota Dewan Perwakilan Daerah Republik Indonesia - Nusa, Jenian P; Pietersz, Jemmy Jefry; Piris, Hendry John (PATTIMURA Law Study Review, 2024)
ABSTRACT: According to Law Number 17 of 2014 as amended in Law Number 14 of 2014 concerning MD3, specifically Article 302 paragraphs 1 and 2 states that DPD members are prohibited from holding concurrent positions if the position in question is as another state official or as a leader. Organizations financed by the State Revenue Budget/Regional Revenue Budget. The problem that then emerged was that there was a case that occurred in a DPD member who held the same position as leader of a political party, so this clearly violated the regulations regarding the DPD being prohibited from holding concurrent positions. For this reason, the implementation of the practice of holding multiple positions by DPD members as leaders of political parties is not in accordance with Law Number 17 of 2014. The aim of this research is to find out and analyze the dual position of a DPD member as a political party leader. The research used in this paper is normative legal research. The results of this research explain that the dual positions held by DPD members are contrary to statutory regulations which ignore Article 302 paragraphs 1 and 2 of Law Number 17 of 2014 as amended in Law Number 14 of 2014 concerning MD3 regarding the prohibition of holding multiple positions for DPD members and the legal consequences of holding multiple positions for DPD members as leaders of political parties. They will be dismissed in accordance with the regulations that apply to DPD members who hold multiple positions.